Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, Intensitas Modal Dan Pertumbuhan Penjulan Terhadap Tax Avoidance - Eka Afrilian Hady Saputra; Mujiyati Mujiyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to examine the influence of profitability, leverage, firm size, capital intensity, and sales growth on tax avoidance. The data utilized in this study are secondary data in the form of financial reports or annual reports of manufacturing companies in the food and beverage industry subsector listed on the Indonesia Stock Exchange during the period 2020-2022. The population used in the study comprises all companies listed on the Indonesia Stock Exchange (IDX) with financial reports. The data collection method employed in this research is documentation method. By conducting panel data regression testing using SPSS 25, the results indicate that profitability and capital intensity ratio significantly affect tax avoidance. Meanwhile, leverage, firm size, and sales growth do not have an effect on tax avoidance. Keywords: Capital Intensity, Company Size, Leverage, Profitability, Sales Growth